PERAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENINGKATKAN MOTIVASI BELAJAR PESERTA DIDIK DI SMPN 26 BANDAR LAMPUNG - Surya, Lukman (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
The purpose of this study was to describe how the role of Islamic Religious Education (PAI) teachers in increasing the learning motivation of students at SMPN 26 Bandar Lampung. The type of research used in this research is descriptive qualitative. In collecting data the researchers used several techniques including the methods of observation, interviews and documentation. The results of this study conclude that the efforts of Islamic religious education teachers in increasing student learning motivation at SMPN 26 Bandar Lampung include: The role of PAI teachers in increasing students' motivation to gain knowledge in PAI lessons at SMPN 26 Bandar Lampung. namely by: (a) providing guidance. (b) realizing and implementing healthy, safe, and attractive classroom conditions (c) conducting evaluations. The difficulties and solutions of PAI teachers in increasing students' learning motivation in learning Islamic religious education at SMPN 26 Bandar Lampung are caused by 2 factors, namely 1) obstacles that come from students: if learning motivation is not found in the students themselves, the desire to learn will be hard to get. Because there is no interest in learning, students will feel lazy to study, ignore lessons, disturb friends in class, skip class and come late and so on. 2) obstacles that come from outside the students themselves: (a.) obstacles come from the family (b.) obstacles come from the community environment (c) obstacles come from the school environment.